Rapid and economic synthesis of bone like apatite using simulated body fluid (SBF). (16th April 2019) - Bhatt, Akshay; Anbarasu, Anand
Abstract: Hydroxyapatite (HAp) is a major mineral component of bones which has excellent bioactivity and biocompatibility making it suitable for various biomedical applications. However, the chemical composition of HAp varies from that of native bones in its Ca/P ratio and with respect to other trace elements. Therefore, when compared to HAp the development of bone-like apatite is of great importance for bone and dental applications. Most of the protocols use Tris hydroxyl amino methane for the preparation of SBF which is expensive. In this study, we have made an attempt to synthesize the bone-like apatite in within a shorter duration (6hrs), without adding tris in SBF, while at the same time, using CaCl2 as a calcium precursor and Na2 HPO4 as a phosphate precursor. The physiochemical properties of the synthesized bone-like apatite were studied. X-Ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy, and thermal analysis were used to verify our results.